Pengukuran Kelelahan dan Power Pemain Sepakbola - Risma, Risma; Nursasih, Isna Daniyati; Rustiawan, Hendra; Hartono, Tony (Jurnal Keolahragaan, 2023)
The purpose of this study was to determine the state of fatigue and power to run on soccer players. This type of research was quantitative descriptive. The research method used was a survey method with test and measurement techniques. The population used was students who are members of the Galuh Ciamis University football team, totaling 42 men. The sampling technique used was total sampling. The instrument test used was a 30 meter sprint fatigue-power maintenance test. The statistical analysis used was descriptive percentages. The results of this study indicate that the average fatigue and power running into the sufficient category consists of 8 players in the sufficient category by 33.3%, 4 players in the excellent category by 16.7%, 5 players in the good category by 20.8%, 3 players 12.5% poor categories, and 4 very poor players category 16.7%. These results have not been maximized, and the physical condition coach must be able to create a training program with a recovery program with the aim that fatigue during training can even be reduced so that there was no fatigue that could caused injury. This research was expected to be a consideration for physical condition coaches in developed training programs to be able to reduced fatigue and increased strength and speed so as to produce sprinting power for football players and as a recommendation for the development of science, especially in the physical condition of soccer players.